Powder X-ray characterization of lithium thiazoildine-4-carboxylate - Antonio, S. G. [UNESP]; Paiva-Santos, C. O. [UNESP]; Corbi, P. P.; Massabni, Antonio Carlos [UNESP]; Andrade, F. C. [UNESP] (J C P D S-int Centre Diffraction Data, 2009)
Powder X-ray diffraction studies of a lithium salt of thiazolidine-4-carboxylic acid (Li-TC4) of composition LiC(4)H(6)NSO(2) are presented in this paper. Analysis of the synchrotron powder X-ray diffraction data showed that the complex has an orthorhombic symmetry with space group P2(1)2(1)2(1). Unit cell parameters after the refinement using the Pawley method are: a=19.4931(3) angstrom, b=4.947 77(6) angstrom, c=6.201 64(8) angstrom, and V=598.051 angstrom(3). (C) 2009 International Centre for Diffraction Data. [DO[: 10.1154/1.3076131]
Keywords: X-ray; powder diffraction; amino acids; thiazolidine-4-carboxylic acid